Association between Interleukin-5 & Body Mass Index among Iraqi Asthmatic Patients - Yacoob Y. Al-Rubayei; Batool A. Al-Haidary; Wala'a E. Jasim (مجلة كلية الطب, 2007)
Background: Asthma is an allergic hypersensitivity disease in which many mediators play a role in its pathogenecity. One of these etiological agents is the mediators such as Interleukin-5 (IL-5).